Oxygen content control in metal injection molding of 316L austenitic stainless steel using water atomized powder. (February 2020) - Yu, Kaiping; Ye, Shulong; Mo, Wei; Lv, Yonghu; Jiang, Heng; Ma, Rui; Kwok, Chi Tat; Yu, Peng
Abstract: 316 L stainless steel samples are fabricated using metal injection molding in which water atomized 316 L powder containing 4200 ppm oxygen is used as the raw material. Oxygen not only hampers the sintering process but also proves to be detrimental to the ductility and corrosion resistance of the sintered sample. It is found that when the 316 L powder is doped with small amount of graphite (0, 500, 1000, 1500 and 2000 ppm), its oxygen content can be effectively reduced via the carbon-oxygen reaction during sintering. As the carbon dosage increases from 0 to 1500 ppm, the sintered density, elongation and pitting potential of the sintered samples are effectively improved due to the decreased oxygen contents in them. However, when 2000 ppm graphite is added, the sample becomes overdosed with carbon. The excessive carbon remains in the material and forms carbon-rich particles during sintering, which has significant adverse effects on the sintering process as well as the ductility and corrosion resistance of the sintered sample.